Cerium oxide nanoparticles (CeO2-NPs) improve growth parameters and antioxidant defense system in Moldavian Balm (Dracocephalum moldavica L.) under salinity stress - Mona Hasan Zadeh Mohammadi; Sima Panahirad; Anahita Navai; Mohammad Kazem Bahrami; Muhittin Kulak; Gholamreza Gohari (Plant Stress, 2021)
Salinity stress is one of the most destructive stress factors causing adverse impacts on growth and productivity of crops plants. In order to combat or to make crop plants compatible with salinity stress, many attempts have been made to alleviate the devastating impacts of salinity stress on plants. Of those attempts, engineered nano-particles (NPs) have gained great interest in recent years, having been tested in a number of crop plants; however, they remain to be investigated for medicinal and aromatic plants. For that reason, the interaction effects of cerium oxide NPs (CeO2 NPs at 25, 50 and 100 mg L−1) and salinity stress (50 and 100 mM NaCl) on Moldavian balm (Dracocephalum moldavica L.) was evaluated. Salinity significantly decreased agronomic traits such as leaf and shoot fresh and dry weight, photosynthetic pigment content and SPAD, whereas it increased MDA, H2O2 and proline (Pro) content, electrolyte leakage (EL) and antioxidant enzymatic activities (SOD, APX and GP). However, CeO2-NP treatments enhanced growth performance of the plants exposed under salinity stress by improving agronomic traits, photosynthetic pigment content, SPAD, Pro, and antioxidant enzymes. Furthermore, CeO2-NPs caused a decrease in MDA, H2O2 and EL via higher antioxidant enzymatic activity under salinity conditions. Of the concentrations of CeO2-NPs tested, 50 mg L−1 concentration gave the best results under both non-stress and salt-stress conditions. In conclusion, foliar spray of CeO2-NP treatments in Moldavian balm improved plant performance under salinity and may be considered as a promising treatment in alleviating the effects of salt stress.